Functional limitations 12 months after SARS-CoV-2 infection correlate with initial disease severity: An observational study of cardiopulmonary exercise capacity testing in COVID-19 convalescents. (October 2022) - Steinbeis, Fridolin; Knape, Philipp; Mittermaier, Mirja; Helbig, Elisa Theresa; Tober-Lau, Pinkus; Thibeault, Charlotte; Lippert, Lena Johanna; Xiang, Weiwei; Müller-Plathe, Moritz; Steinbrecher, Sarah; Meyer, Hans-Jakob; Ring, Raphaela Maria; et al.
Abstract: Background: Cardiopulmonary Exercise Testing (CPET) provides a comprehensive assessment of pulmonary, cardiovascular and musculosceletal function. Reduced CPET performance could be an indicator for chronic morbidity after COVID-19. Methods: Patients ≥18 years with confirmed PCR positive SARS-CoV-2 infection were offered to participate in a prospective observational study of clinical course and outcomes of COVID-19. 54 patients completed CPET, questionnaires on respiratory quality of life and performed pulmonary function tests 12 months after SARS-CoV-2 infection. Results: At 12 months after SARS-CoV-2 infection, 46.3% of participants had a peak performance and 33.3% a peak oxygen uptake of <80% of the predicted values, respectively. Further impairments were observed in diffusion capacity and ventilatory efficiency. Functional limitations were particularly pronounced in patients after invasive mechanical ventilation and extracorporeal membrane oxygenation treatment. Ventilatory capacity was reduced <80% of predicted values in 55.6% of participants, independent from initial clinical severity. Patient reported dyspnea and respiratory quality of life after COVID-19 correlated with CPET performance and parameters of gas exchange. Risk factors for reduced CPET performance 12 months after COVID-19 were prior intensive care treatment (OR 5.58, p = 0.004), SGRQ outcome >25 points (OR 3.48, p = 0.03) and reduced DLCO (OR 3.01, p = 0.054). Conclusions: Functional limitations causing chronic morbidity in COVID-19 survivors persist over 12 months after SARS-CoV-2 infection. These limitations were particularly seen in parameters of overall performance and gas exchange resulting from muscular deconditioning and lung parenchymal changes. Patient reported reduced respiratory quality of life was a risk factor for adverse CPET performance. Graphical abstract: Image 1 Highlights: Functional limitations 12 months after SARS-CoV-2 infection are associated with initial COVID-19 severity. Cardiopulmonary performance is reduced in 46% of patients 12 months after acute COVID-19. Gas exchange remains impaired 12 months after ICU treatment. Functional limitations improve between month 6 and 12 in some patients.